The direction of work flow matters: influence mechanism of task interdependence on employee proactive work behavior - Yu, Ting; Zhao, Yanmei; Zhang, Zhengtang (Frontiers in Psychology, 2023)
Given the increasing uncertainty in today’s environment, how enterprises implement changes to stimulate employee proactive work behavior has become an important practical topic in the human resources field. This study considers work flow direction and refers to the work characteristic and job demand–resource models to explore the influence of task interdependence (initiated and received) on employee proactive work behavior. We interviewed human resource staff and surveyed employees of an internet company headquartered in Jiangsu, China. The empirical results show that initiated task interdependence has a positive impact on employee proactive work behavior, and task significance plays a mediating role between them. Self-esteem does not affect the positive relationship between initiated task interdependence and task significance, nor does it influence the aforementioned mediating effect of task significance. Moreover, received task interdependence has no significant effect on proactive work behavior, and task significance has no significant mediating effect between them. Self-esteem moderates the relationship between received task interdependence and task significance. Specifically, when self-esteem is low, received task interdependence positively predicts task significance, and when self-esteem is high, the received task interdependence–task significance relationship is not significant. Furthermore, self-esteem moderates the mediating effect of task significance between received task interdependence and proactive work behavior. Specifically, when self-esteem is low, task significance plays a mediating role but not when self-esteem is high. Theoretical contributions and managerial implications are discussed.